Os descaminhos de Mnemosine: exílio e memória na obra de Elisa Lispector - Jacintho, Nicolas Ferreira Neves (2022)
The research aims to study the way in which the themes of memory and exile intertwine in the novels Além da Fronteira (1945) and No exílio (1948), both by Elisa Lispector and inserted in a context of literary production connected to the displacement of Jewish families to Brazil during the first decades of the 20th century. The literature that flourished at that time built an imaginary geography derived from the impossibility of returning and based on some thematic and narrative elements linked to exile and memory. Therefore, it is proposed as a hypothesis that the novels to be analyzed are structured through narrativized memories, so that the reflections of Maurice Halbwachs in A memória coletiva (2006), and of Paul Ricoeur on memory as a narrative operation, as proposed in A memória, a história, o esquecimento (2007) will be central to this dissertation. Finally, thanks to the relationship between memory and exile, Maria José de Queiroz's analysis of exile in Os males da ausência ou a literatura do exílio (1998) will be extremely importante for the progress of this work, as well as the reflections of George Simmel in O estrangeiro (2005) and Donatella di Cesare in Estrangeiros residentes (2020).